Tailoring Electrocatalytic Properties of sp2-Bonded Carbon Nanoforms Through Doping - Paweł Szroeder; Agnieszka Banaszak-Piechowska; Ihor Sahalianov (Molecules)
The symmetry of the valence and conduction bands in graphene and carbon nanotubes allows for easy modification of the electronic structure, which is correlated with their electrocatalytic activity. Modifying the electronic structure of the sp2-bonded nanocarbons by substituting carbon atoms with electron donors/acceptors and through covalent functionalization can facilitate heterogeneous electron transfer (HET), which is beneficial for designing carbon-based, high-performance electrocatalysts. Based on the Gerischer–Marcus model, we discuss how we can match the density of π-electron states (DOS) of a nanocarbon electrode to the redox potential of redox species using electron and hole doping. Along with the results, this article provides guidance on how to match the properties of nanocarbons to specific electroactive analytes, oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), and oxygen evolution reaction (OER).